To Study the Efficacy of Soft Tissue Release Manual Therapy Techniques in Patients with Moderate COPD.: Life Sciences-Physiotherapy - Dutta, Abhijit (International Journal of Life Science and Pharma Research, 2021)
Apart from pulmonary manifestations Chronic Obstructive Pulmonary Disease (COPD) includes extra pulmonary manifestation like altered chest wall mechanics and musculoskeletal dysfunction. There are many studies that have described the effect of manual therapy in musculoskeletal structural changes in isolation among people with COPD, although the influence of soft tissue manual therapy techniques on chest expansion and pulmonary function remains largely unclear. Therefore, the study was proposed with combined soft tissue protocol to address the involved soft tissue structure in COPD. To find the effectiveness of soft tissue release manual therapy techniques (STRMTT) on improvement of chest expansion and Pulmonary function- FEV1/FEV6 in patients with moderate COPD. This is a comparative study design with two groups- Experimental Group and Control Group, conducted on a total 20 subjects, 10 in each group. The Experimental group subjects were treated with soft tissue release manual therapy techniques along with conventional treatment whereas control group subjects were treated with only conventional exercises. Both the group subjects received treatment twice in a week for a period of eight weeks. The outcome measures Chest expansion and pulmonary function FEV1/FEV6 was measured at before intervention and after 8 weeks of intervention. Comparative analysis of post intervention means using Independent ‘t’ test between the groups found statistically significant difference (p<0.05) in Chest expansion at Auxiliary level and Xiphisternum level and in FEV1/FEV6 between the groups. It is found from our pilot study that soft tissue release manual therapy techniques addressing the soft tissue structure in subjects with moderate COPD who was treated for a period of 8 weeks along with conventional treatment showed statistically significant effect in improving chest expansion and FEV1/FEV6 when compared with the only conventional exercises.